2019
DOI: 10.1017/s0950268819000384
|View full text |Cite
|
Sign up to set email alerts
|

Modelling diverse sources of Clostridium difficile in the community: importance of animals, infants and asymptomatic carriers

Abstract: Clostridium difficile infections (CDIs) affect patients in hospitals and in the community, but the relative importance of transmission in each setting is unknown. We developed a mathematical model of C. difficile transmission in a hospital and surrounding community that included infants, adults and transmission from animal reservoirs. We assessed the role of these transmission routes in maintaining disease and evaluated the recommended classification system for hospital- and community-acquired CDIs. The reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
(106 reference statements)
1
12
0
Order By: Relevance
“…For this reason, in our study, we excluded these patients from our epidemiological analyses. However, we chose to include isolates from infants in our toxin profiling and antimicrobial susceptibility testing analyses due to the potential for infants to serve as reservoirs of clinically relevant strains of C. difficile ( Rousseau et al., 2012 ; McLure et al., 2019 ). Interestingly, while the prevalence of CDI in older patients (≥60 years) was slightly higher than in the other age groups in our setting, there did not appear to be a strong association of CDI with age that is typically observed in European and US studies.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in our study, we excluded these patients from our epidemiological analyses. However, we chose to include isolates from infants in our toxin profiling and antimicrobial susceptibility testing analyses due to the potential for infants to serve as reservoirs of clinically relevant strains of C. difficile ( Rousseau et al., 2012 ; McLure et al., 2019 ). Interestingly, while the prevalence of CDI in older patients (≥60 years) was slightly higher than in the other age groups in our setting, there did not appear to be a strong association of CDI with age that is typically observed in European and US studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the anaerobic gastrointestinal pathogen Clostridioides difficile has established itself as one of the major causative agents of pseudomembranous colitis and toxic megacolon ( Wiegand et al, 2012 ; Nasiri et al, 2018 ; Martínez-Meléndez et al, 2020 ; Doll et al, 2021 ). C. difficile does not only produce enterotoxins that damage the gastrointestinal epithelium ( Fletcher et al, 2021 ) but also forms easily transmittable spores that significantly contribute to C. difficile’s efficient spreading in the environment, hospitals and elderly homes ( McLure et al, 2019 ; Hernandez et al, 2020 ; Werner et al, 2020 ; Khader et al, 2021 ). If conditions are favorable, e.g., after antibiotic-induced dysbiosis when the reduced microbiome fails to convert primary bile acids into secondary bile acids, C. difficile spores are able to germinate to successively colonize the large intestine ( Theriot et al, 2014 ; Pike and Theriot, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anaerobic gut bacterium Clostridioides difficile (also known as Clostridium difficile (Lawson et al, 2016)) is the most frequent infectious cause of antibiotic-associated diarrhoea and among the leading culprits of healthcareassociated infections (Martin et al, 2016). However, modelling studies have suggested that transmission in the community and in the healthcare system were equally relevant for sustaining C. difficile in the human population (Durham et al, 2016;McLure et al, 2019). Patients asymptomatically colonized with C. difficile upon hospital admission have a sixfold increased risk of suffering a C. difficile infection (CDI) (Zacharioudakis et al, 2015), and even without developing CDI themselves they may increase the overall burden of nosocomial CDI significantly by spreading the pathogen to other patients (Longtin et al, 2016;Blixt et al, 2017;Donskey et al, 2018).…”
Section: Introductionmentioning
confidence: 99%